Potential Role of Autonomic Dysfunction in Covid-19 Morbidity and Mortality - Del Rio, Rodrigo; Marcus, Noah J.; Inestrosa, Nibaldo C. (My University, 2020)
OPINION article Front. Physiol., 16 October 2020Sec. Clinical and Translational Physiology Volume 11 - 2020 | https://doi.org/10.3389/fphys.2020.561749
Keywords: autonomic nervous system; covid-19; inflammation; sympathetic nervous system; parasympathetic; sympathetic reactivity